Methods of Assessing the Competitive Environment of Public Food Service Establishments in the Context of Providing their Sustainable Development - KUZNETSOVA, Nina Vladimirovna; VASILYEVA, Anastasiya Grigoryevna; RAHIMOVA, Liliya Muhametovna; ORININA, Larisa Vladimirovna; KASHUBA, Inessa Valerjevna; KIVA-KHAMZINA, Yuliya Leonidovna (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017, 2017)
In the context of modern economic development, the ability of domestic enterprises to effectively position and develop their competitive advantages under the conditions of global competition becomes important for Russia. The strategy of economic reform that unfolded in Russia in recent years, involves the comprehensive development of new economic relations in all sectors of the national economy, the formation of flexible and adaptive management system and the creation of conditions necessary for effective business activities. As practice shows, the majority of domestic enterprises are not ready to compete actively, which leads to deterioration of enterprises’ performance. Improvement of the situation is possible only in the presence of competitive products focused on the needs of the consumer. In this case, the organization's competitiveness is an essential condition for the survival and sustainable development in a competitive and volatile external environment. To solve the problems set in the work the systemic, the structural and functional approaches, special methods of sociological research, tabular and graphical visualization methods of research results were used. Findings of the study can be applied by Public Food Service Establishments (PFSE) to provide sustainable development and improve the efficiency of economic activity in a changing external environment.